At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

(-3.2)^0 write two expressions equivalent to the given expression

Sagot :

Step-by-step explanation:

First expression

[tex] = {( - 3 \times 2)}^{0} [/tex]

[tex] = { - 3}^{0} \times {2}^{0} [/tex]

[tex] = 1 \times 1[/tex]

[tex] = 1[/tex]

[tex] \: [/tex]

Second expression

[tex] = {( - 3 \times 2)}^{0} [/tex]

[tex] = { - 6}^{0} [/tex]

[tex] = 1[/tex]

[tex] \: [/tex]

third expression

[tex] = {( - 3 \times 2)}^{0} [/tex]

[tex] = {( - 3 \times 2)}^{1 - 1} [/tex]

[tex] = \frac{ - 3 \times 2}{ - 3 \times 2} [/tex]

[tex] = \frac{ - 6}{ - 6} [/tex]

[tex] = 1[/tex]